"Don't Call Us, We Call You" - A Community Driven Approach for (Domain Independent) Context Driven Information Retrieval (CoDIR) - Beul, Michael; Eicker, Stefan (The Fifth International Conference on Signal Image Technology & Internet Based Systems - SITIS 2009, 2010)
This paper discusses the combination of context injection, metadata enrichment and information broking with current semantic web and community oriented concepts in order to optimize the search and retrieval process of relevant information. The presented approach focuses the shift from information pull to information push, and thus reduces the effort on finding the needed information for a specific issue in a concrete context.
Keywords: knowledge management; semantic searching; context driven; semantic web; information retrieval